Deep reinforcement learning for AoI minimization in UAV-aided data collection for WSN and IoT applications: a survey - Ahmed Amodu, Oluwatosin; Jarray, Chedia; Raja Mahmood, Raja Azlina; Althumali, Huda; Ali Bukar, Umar; Nordin, Rosdiadee; Abdullah, Nor Fadzilah; Cong Luong, Nguyen (Institute of Electrical and Electronics Engineers, 2024)
Deep reinforcement learning (DRL) has emerged as a promising technique for optimizing the deployment of unmanned aerial vehicles (UAVs) for data collection in wireless sensor networks (WSNs) and Internet of Things (IoT) applications. With DRL, UAV trajectory can be optimized, optimal data collection points can be determined, sensor node transmissions can be scheduled efficiently, and irregular traffic patterns can be learned effectively. In view of the significance of DRL for UAV-assisted IoT research in general and, more specifically, its use for time-critical applications, this paper presents a review of the existing literature on UAV-aided data collection for WSN and IoT applications related to the application of DRL to minimize the Age of Information (AoI), a recent metric used to measure the degree of freshness of transmitted information collected in data-gathering applications. This review aims to provide insights into the state-of-the-art techniques, challenges, and opportunities in this domain through an extensive analysis of a sizable range of related research papers in this domain. It discusses application areas of UAV-assisted IoT, such as environmental monitoring, infrastructure inspection, and disaster response. Then, the paper focuses on the proposed works, their optimization objectives, architectures, simulation libraries and complexities of the various DRL-based approaches used. Thereafter discussion, challenges, and some opportunities for future work are provided. The findings of this review serve as a valuable resource for researchers and practitioners, guiding further advancements and innovations in the field of DRL for UAV-aided data collection in WSN and IoT applications.